Managing Type 2 diabetes as a couple: The influence of partners' beliefs on diabetes distress over time. (July 2018) - Berry, Emma; Davies, Mark; Dempster, Martin
Highlights: Diabetes beliefs held by couples living with Type 2 diabetes influence emotional wellbeing. Partners' beliefs have an indirect impact on diabetes distress in their loved ones with diabetes. The direct and indirect effects of diabetes beliefs on emotional distress endure overtime. Abstract: Aims: Partners and spouses have an important role in supporting healthy self-care in adults with Type 2 diabetes. While evidence has shown that the beliefs held by people with diabetes influence emotional wellbeing, little is known about the long-term impact of partners' illness beliefs on diabetes distress. Methods: Persons with Type 2 diabetes (pwt2d) and their partners completed a questionnaire at baseline (N = 75 couples) and 12 months later (N = 45 couples). Measures included demographic/clinical parameters, the Revised Illness Perception questionnaire, and the Diabetes Distress Scale. A repeated measures ANOVA was used to examine change in measures over time. Multiple regression and moderation analysis were used to explore the indirect influence of partners beliefs on diabetes distress at baseline and follow-up. Results: Illness perceptions and diabetes distress in pwt2d and partners did not change overtime. Partners' beliefs about the controllability, chronicity, and predictability of symptoms of diabetes moderated the relationship between the corresponding pwt2d beliefs and diabetes distress. These indirect effects were observed across both time points. Conclusions: Conflicting illness perceptions about the controllability and chronicity of diabetes, and congruous negative perceptions about diabetes symptoms among couples sustain distress overtime. Targeting the beliefs of couples to improve communication and understanding may reduce diabetes distress.